Polyester-based photocrosslinkable bioadhesives for wound closure and tissue regeneration support - Santos, M. (2021)
Photocrosslinkable surgical adhesives provide many advantages when compared with traditional methods used in wound closure. This work aimed to develop UV-curable biodegradable adhesives based on lactic acid and PCL oligomers. Both materials were functionalized with 2-isocyanatoethyl acrylate (AOI). Subsequently, the photoinitiator (Irgacure® 2959) was added to the blend and then, the final materials were irradiated under UV light for two different times: 30 s and 2 min. After production of adhesives, its physicochemical properties were evaluated through FTIR-ATR and TGA, as well as its rheology, dynamic water contact angle, swelling capacity and hydrolytic degradation. Furthermore, the biocompatibility of the produced adhesives was also characterized in contact with human dermal fibroblasts cells. The antimicrobial activity of the materials was assessed by using Staphylococcus aureus and Escherichia coli, as bacterial models.